Blind signatures from Zero knowledge in the Kummer variety - Barreto, Paulo L.; Reich, Devin D.; Simplicio Jr., Marcos A.; Zanon, Gustavo H. M. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2023: Anais do XXIII Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2023.233503, 2023)
We show how to apply the BZ methodology (Blind signatures from Zero knowledge) to obtain blind signatures in the Kummer varieties defined by Montgomery curves. We also describe specially-tailored arithmetic algorithms to facilitate its efficient implementation. The result can be proved secure under appropriate assumptions, appears to resist even the ROS attack (to which most elliptic-curve blind signature schemes succumb), and is arguably one of the most efficient among those proposals that offer similar security guarantees.